Evaluation of air quality in the surrounding community due to limestone blasting - Ahmad Zawawi, Emma Marinie; Wan Ibrahim, Wan Hasmirah; Muhammad Salleh, Naziah; Daud, Badrul Hisham (UiTM Press, 2025)
Air quality is very important in the people’s lives. In Malaysia, the quality of air needs to be monitored as the level is getting worst day by day. This is especially the case in areas where activities such as construction and quarry mining operate actively. This paper presents the findings of an investigation into air quality status in a community adjacent to a quarry. Air pollutants were monitored according to PM2.5 and PM10, using the TSI 8533 DustTrak, DRX Desktop Aerosol Monitor. The data were used to examine the influence of mining activities (blasting and non-blasting) within variability of PM2.5 and PM10 concentrations inside residential buildings. Indoor dust was collected manually to be tested in the lab to identify the chemical composition. The result indicates that within-day variability of indoor PM2.5 and PM10 was influenced by the occupant’s activities and surrounding outdoor activities such as blasting and vehicle movements. Mitigation measures are proposed to ensure the achievement of sustainable development and indirectly improve the quality of air around the nearby residential area. It is anticipated that both residents and the quarry management are aware of the importance of monitoring air quality towards sustainable life in the future.